2019
DOI: 10.1103/physrevb.99.134511
|View full text |Cite
|
Sign up to set email alerts
|

Electron-phonon coupling and superconductivity-induced distortion of the phonon lineshape in V3Si

Abstract: Phonon measurements in the A15-type superconductors were complicated in the past because of the unavailability of large single crystals for inelastic neutron scattering, e.g. in the case of Nb3Sn, or unfavorable neutron scattering properties in the case of V3Si. Hence, only few studies of the lattice dynamical properties with momentum resolved methods were published, in particular below the superconducting transition temperature . Here, we overcome these problems by employing inelastic x-ray scattering and rep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Among the best studied representatives are the charge-density-wave (CDW) compounds [34][35][36][37][38][39] and the binary A15 compounds [105,106] displaying low-dimensional and three-dimensional structural motifs, respectively. Similar to our results for Sc 3 CoC 4 above, many of these superconducting materials have been found to undergo phonon softening processes towards their structural phase transition temperatures [34,62,90,91,96,97,[105][106][107][108][109][110][111][112][113][114][115]. Furthermore, the structural and superconducting phase transitions in Sc 3 CoC 4 , CDWs and A15 compounds are susceptible to a manipulation by means of applied strain or hydrostatic pressure [34-36, 40-44, 51, 52, 57, 105, 111, 116-118].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Among the best studied representatives are the charge-density-wave (CDW) compounds [34][35][36][37][38][39] and the binary A15 compounds [105,106] displaying low-dimensional and three-dimensional structural motifs, respectively. Similar to our results for Sc 3 CoC 4 above, many of these superconducting materials have been found to undergo phonon softening processes towards their structural phase transition temperatures [34,62,90,91,96,97,[105][106][107][108][109][110][111][112][113][114][115]. Furthermore, the structural and superconducting phase transitions in Sc 3 CoC 4 , CDWs and A15 compounds are susceptible to a manipulation by means of applied strain or hydrostatic pressure [34-36, 40-44, 51, 52, 57, 105, 111, 116-118].…”
Section: Discussionsupporting
confidence: 85%
“…In line with the condensation of a zone-center phonon mode [114,115], the symmetry reduction in V 3 Si and Nb 3 Sn from space group P m3n to space group P 4 2 /mmc involves only a translationengleiche (t3) step and no doubling of the unit cell volume [106,[124][125][126] like in the HT-LT transition of Sc 3 CoC 4 . The structural changes due to the tetragonal distortion of the A15 compounds therefore do not allow an alternative description by a commensurate or incommensurate displacive modulation of the cubic parent phase.…”
Section: Discussionmentioning
confidence: 85%
“…We speculate that a structural phase transition may have occurred at T * in the high-content cobalt-doped samples (x ⩾ 0.15). Previous studies have shown a martensitic cubic to tetragonal phase transition at a temperature of about 18.9 K in the V 3 Si compound [16][17][18][19]. Besides, the hydrostatic pressure will gradually suppress this martensitic phase transition [36,37].…”
Section: Resultsmentioning
confidence: 93%
“…These include the anisotropy of the upper critical field and specific heat, De Hass-Van Alphen effect, and large ratio of T c with Fermi temperature (T F ). Strong evidence exists that a martensitic cubic to tetragonal phase transition occurs at about 18.9 K, slightly above the T c [16][17][18][19]. Unusual softening of the acoustic phonons in V 3 Si has been reported [20,21].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation